Cardiovascular Health Status and Incidence of Heart Failure in the Framingham Offspring Study. (January 2016) - Nayor, Matthew; Enserro, Danielle M.; Vasan, Ramachandran S.; Xanthakis, Vanessa
Abstract : Background—: The American Heart Association Cardiovascular Health (CVH) score is inversely associated with cardiovascular disease, but its relations to cardiac remodeling traits and heart failure (HF) incidence have not been examined. Methods and Results—: A 14-point score was constructed for each participant based on the presence of poor, intermediate, or ideal status on each of the 7 CVH metrics (ideal score=14). We related the CVH score to echocardiographic traits cross-sectionally and to HF incidence prospectively in the Framingham Offspring Study. In age- and sex-adjusted models, a higher CVH score was associated with lower left ventricular (LV) mass, LV wall thickness, LV diastolic dimension, and left atrial dimension ( P <0.01 for all; n=2392; mean age, 58 years; 56% women), and with a 12% to 15% lower odds of prevalent LV concentric remodeling and concentric hypertrophy, respectively ( P <0.0001 for both). On follow-up (mean, 12.3 years), 188 incident HF events were observed in 3201 participants (mean age, 59 years; 53% women). In age- and sex-adjusted Cox proportional hazard models, the CVH score was inversely associated with HF incidence (hazard ratio per 1-point higher CVH score, 0.77; 95% confidence interval, 0.72–0.83). This association was partially attenuated upon adjustment for LV mass and interim myocardial infarction (hazard ratio, 0.84; 95% confidence interval, 0.76–0.93), and it was consistent for HF with preserved and reduced ejection fractions. Conclusions—: In our community-based sample, comprised predominantly of middle-aged white individuals of European descent, better CVH was associated with lower HF incidence, in part due to a lower prevalence of adverse cardiac remodeling. Abstract : Supplemental Digital Content is available in the text.